Students attitudes on STACK content: A pilot study at the university of Trieste, Italy - Zevick Otieno Juma; Elisabetta Chelleri; Daniel Doz; Danilo Lewanski (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: Online examinations are increasingly prevalent in educational settings, offering innovative assessment methods. Understanding student perceptions and experiences with such systems is essential for enhancing their effectiveness and acceptance in educational practice.Aims: This pilot study aimed to examine the impact of STACK-based online exams on various facets such as student comfort, perceived value for learning and exam preparation, preferences between pen-and-paper versus STACK formats, confidence in online math tests, readiness to adopt online assessment platforms, and overall perspectives on online evaluations.Method: An experimental within-subjects design and convenience sampling were used to involve 117 first-year biology students enrolled in a Probability and Statistics course, who were already familiar with the STACK system. Data were collected using pre- and post-exam online surveys featuring five-point Likert scale questions and an open-ended query.Results: The findings indicate that students felt more comfortable using the STACK system after the study and preferred it over traditional exams. Nevertheless, some students expressed uncertainty about using STACK content for final exams due to concerns about its effectiveness in evaluating critical thinking and potential technical difficulties. However, concerns regarding technical challenges decreased significantly post-exam, with no technical issues reported during the exam. Positive feedback highlighted STACK's benefits for formative assessment, easier learning, immediate feedback, and its practicality and innovation. Some students even suggested incorporating STACK into final exams for convenience and advocated for further investment in the STACK system, possibly with improved content. Conclusion: In summary, students preferred using STACK for exams, though concerns about technical glitches and the need to refine content for assessing critical thinking persist. Future efforts should focus on enhancing content quality, starting this summer.